Seasonal and Spatial Variability in the Biogenic Production and Consumption of Volatile Organic Compounds (VOCs) by Marine Plankton in the North Atlantic Ocean - Davie-Martin, Cleo L.; Giovannoni, Stephen J.; Behrenfeld, Michael J.; Penta, William B.; Halsey, Kimberly H. (Frontiers in Marine Science, 2020)
Marine-derived volatile organic compounds (VOCs) influence global carbon cycling, atmospheric reactions, and climate. Yet, the biogenic production (sources) and consumption (sink) rates of marine VOCs are not well-constrained and are currently excluded from global chemical transport models. We directly measured the net biogenic production rates of seven VOCs (acetaldehyde, acetone, acetonitrile, dimethylsulfide, isoprene, methanethiol, and methanol) in surface seawater during four field campaigns in the North Atlantic Ocean that targeted different stages of the phytoplankton annual cycle. All of the VOCs exhibited strong seasonal trends, with generally positive rates during May (peak spring bloom) and lower, sometimes negative rates (net consumption), during November and/or March (the winter bloom minimum transition). Strong latitudinal gradients were identified for most VOCs during May and September, with greater production observed in the northern regions compared to the southern regions. These gradients reflect the interplay between high phytoplankton and bacterial productivity. During the bloom transition stages (March and September), acetaldehyde and acetone exhibited net production rates that bracketed zero, suggesting that biogenic production was either very low or indicative of a tightly coupled system with more complex underlying microbial VOC cycling. Our data provides the first direct evidence for widespread biogenic acetonitrile production and consumption in the surface ocean and the first net biogenic production rates for methanethiol in natural seawater.